2018
DOI: 10.1002/adom.201800985
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar Graphene–Quantum Dot Phototransistors with CMOS Compatibility

Abstract: The hybridization of 2D materials and colloidal quantum dots (CQDs) has been demonstrated to be an ideal platform for infrared photodetectors due to the high mobility of 2D materials and the excellent light harvesting capability of CQDs. However, the realization of ambipolar, broadband, and room‐temperature graphene–quantum dot phototransistors with complementary metal–oxide–semiconductor (CMOS) compatibility remains challenging. Here N, S codecorated graphene is deposited with PbS CQDs to fabricate a hybrid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…To overcome this problem, N, S co-decorated graphene fabricated by chemical vapor deposition (CVD) was also deposited with PbS CQDs to fabricate a hybrid phototransistor with CMOS compatibility (Figure 9g). [77] P-type doping can be effectively inhibited by N, S co-decorating. As a result, the required gate voltage can be reduced to less than 3.3 V that is compatible with CMOS technology (Figure 9h).…”
Section: Cqd/graphene Hybrid Phototransistorsmentioning
confidence: 99%
“…To overcome this problem, N, S co-decorated graphene fabricated by chemical vapor deposition (CVD) was also deposited with PbS CQDs to fabricate a hybrid phototransistor with CMOS compatibility (Figure 9g). [77] P-type doping can be effectively inhibited by N, S co-decorating. As a result, the required gate voltage can be reduced to less than 3.3 V that is compatible with CMOS technology (Figure 9h).…”
Section: Cqd/graphene Hybrid Phototransistorsmentioning
confidence: 99%
“…Similar photoresponses were also observed in graphene/QD photodetectors by others. 14 When the gate voltage is far from the appeared Dirac point on the left side, the conductivity of the graphene device is linear with the gate voltage. A right shift in gate transfer characteristics will result in a constant increase in conductivity, i.e.…”
Section: 𝑞;𝑉mentioning
confidence: 99%
“…10,11,12,13 Coating graphene with semiconducting quantum dots (QDs) can strongly enhance the light absorption and introduce an interesting high photo gain at an order of 10 8 , 14, 15, 16 several orders of magnitude larger than photodetectors based on pure semiconducting QDs (often have a photo gain of 10 2 -10 3 ). 17,18,19 The classical carrier-recycling gain mechanism is often used to explain the origin of high gain, 14,15,16 that is, the high gain originates from the photoexcited carriers circulating the circuits many times before recombination due to the long response time and short transit time. 20 However, this classical gain theory is an implicit function and may even be questionable.…”
mentioning
confidence: 99%
“…Similarly, Zheng et al demonstrated an ambipolar broadband photodetector based on N, S codecorated graphene-PbS quantum dot heterostructure. [42] N, S codecorated graphene greatly reduces the p-type doping of graphene in air. The gate voltage required to modulate the Dirac point and the carrier type is significantly reduced, thereby achieving gate tuneable mutual transformation of positive and negative photoresponse.…”
Section: Konstantatos Et Al Demonstrated a Hybrid Graphene-pbs Quantu...mentioning
confidence: 99%